Accelerated expansion of the Universe in the presence of dark matter pressure - Rezaei, Zeinab (Canadian journal of physics, 2020)
Expansion dynamics of the Universe is an important subject in modern cosmology. The dark energy equation of state determines these dynamics so that the Universe is in an accelerating phase. However, dark matter (DM) can also affect the accelerated expansion of the Universe through its equation of state. In the present work, we explore the expansion dynamics of the Universe in the presence of DM pressure. In this regard, applying the DM equation of state from the observational data related to the rotational curves of galaxies, we calculate the evolution of DM density. Moreover, the Hubble parameter, history of scale factor, luminosity distance, and deceleration parameter are studied while the DM pressure is taken into account. Our results verify that the DM pressure leads to higher values of the Hubble parameter at each redshift and the expansion of the Universe grows due to the DM pressure.